1980
DOI: 10.1148/radiology.134.2.7352231
|View full text |Cite
|
Sign up to set email alerts
|

Gray-scale ultrasonography in the evaluation of renal trauma.

Abstract: Static and real-time gray-scale ultrasound examinations were performed on seven patients who had minor, major, and catastrophic renal trauma. The sonographic findings in avulsion of the renal pedicle, fractured kidney, ruptured renal cyst, perinephric and subcapsular hematomas, and pelvic blood clots are presented. Ultrasonography provided a valuable adjunct to conventional urography and radionuclide studies by adding information on the extent of renal and retroperitoneal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 0 publications
0
4
1
2
Order By: Relevance
“…Without exception, these features could be seen in our patients. Ultrasonography has been recommended as a guod adjunctive study in evaluating renal trauma and excluding post-traumatic renal problems (Kay et a/., 1980). In the present series, US showed perirenal and intrarenal haematomas but, taken in isolation, could not accurately determine the severity of the renal injury.…”
Section: Diagnosiscontrasting
confidence: 58%
“…Without exception, these features could be seen in our patients. Ultrasonography has been recommended as a guod adjunctive study in evaluating renal trauma and excluding post-traumatic renal problems (Kay et a/., 1980). In the present series, US showed perirenal and intrarenal haematomas but, taken in isolation, could not accurately determine the severity of the renal injury.…”
Section: Diagnosiscontrasting
confidence: 58%
“…Kay, Rosenfield and Armm studied the usefulness of gray scale ultrasonography in the evaluation of renal trauma and concluded that the extent of injury to the perirenal and pararenal regions was depicted better with ultrasound than with urography, nuclear medicine or angiography. (6) Thus, USG detected renal trauma in both the cases. It is quick and reliable diagnostic tool in emergency settings.…”
Section: Crossed Fused Ectopiamentioning
confidence: 76%
“…Oblique views of the pelvis project the pelvic kidney away from superimposed skeletal and bowel shadows and are the best means of confirming a pelvic kidney. Kay et al (1980) compared the value of ultrasound and urography in patients with renal trauma but did not discuss pelvic kidneys. The relationship between phimosis and squamous carcinoma of the penis is well established (Kennaway, 1947).…”
mentioning
confidence: 99%